(untitled) (World Science, 2021)
The article presents a strategy for renovation in the riverside area: improvement of water protection functions; rehabilitation of disturbed territories; the use of recreational and urban planning potential of such territories for creating a recreational framework on the waterfront; integration of eco-clusters into the structure of riverside territories and the development of an integrated management system for waterfront zones. As a result of the research, the necessity of rethink the attitude to urban planning within the riverside areas is formulated. Possibilities of sustainable development of riparian territories are determined. Stages of rehabilitation of communal warehousing and industrial territories for sustainable development and rehabilitation of urban areas are proposed. A formalized model of structural renovation of the exploring areas are being built, on the basis of which the identified principles of rehabilitation are being tested. The significance of the obtained results for urban science lies in the development of new approaches to the identification and formation of the structure of territories in the area of interaction with the water area. In the formulation of the basic principles underlying the structural and planning transformations of riparian areas.